Proposed Performance Management System Using Kbpms Framework At PT. Kita Bersama - Utama, Rizki; Wibisono, Dermawan (Journal of Economics and Business UBS, 2024)
In Indonesia, company performance measurement is regulated by standards such as Financial Accounting Standards (SAK) published by the Indonesian Accountants Association (IAI). PT Kita Bersama, which operates in the direct sales sector, has experienced a decline in revenue in the last 5 years. One of the causes is the absence of clear performance indicators for employees so that they work without adequate targets and control. Therefore, this thesis research aims to propose the implementation of an integrated performance management system at PT Kita Bersamawith a focus on product marketing and Key Performance Indicators (KPI). The result is 23 KPIs derived from the company's strategy and business processes to carry out more comprehensive performance measurement and evaluation. Furthermore, the Knowledge Based Performance Management System (KBPMS) is designed to overcome various company challenges related to data integration, employee involvement, alignment of activities with vision and mission, and performance management. KBPMS is also based on five principles to simplify operations, increase efficiency, and drive sustainable growth of the company. By implementing this knowledge management system, it is hoped that company performance can be improved in a structured manner according to long-term targets.